Poverty Alleviation in Bangladesh:ccess Story of Grameen Bank? - Mahjabeen, Rubena (2008)
In October 2006, Professor Mohammad Yunus received the Nobel Peace Prize in collaboration with Grameen Bank for the unique concept micro credit. This concept is now widely recognised and practiced all over the world as an effective instrument for alleviating poverty. Grameen Bank is originated in Bangladesh, poverty stricken developing country, which suffers from continues natural as well as manmade disasters every year. Even though over the last few decades the discussions on microfinance institutions and microcredit have been there all the time, the Nobel Peace Prize turned the focus on the concept more vigorously than ever before. Hence, in this thesis it is interesting to look at the background of Bangladesh in a nut shell, the political, social, economical and the technological aspects of the country to be more precise. In doing so, we have the background for how Professor Yunus, rightly recognised as a social entrepreneur, came up with the unique and amazing idea of microcredit by providing only US$27 to 42 women in a rural village of Bangladesh. Even to his amazement Professor Yunus found out that every penny he lent out was paid out by those women whom he had lent the money. Eventually after much struggling and persuasion in vain to many commercial financial institutions, Professor decided to fabricate a separate financial institution, namely the microfinance institution, which is owned by the borrowers with only 6% owned by the Bangladesh Government. Subsequently, what started as an experiment, started to flourished and expanded rapidly throughout the country. Other countries also started to replicate the Grameen programmes as tool for alleviating poverty. However, the institution also faced much dreaded criticisms from many critiques throughout the world as well despite of its success and popularity among many. Some critiques questioned the institutions economical viability while other expressed their concerns about the social impacts the programmes has in a community, more precisely regarding empowerment of poor women borrowers who are the majority of the clients the institution have. Nevertheless, with all these critical discussions one cannot ignore the impact microcredit and microfinance has over alleviation of poverty, no matter how insignificant it looks at the present. At least we can say that it is the first step towards the development if not the end of the journey. Moreover, microfinance is not the magic trick that would magically make disappear all the problems with just a flick of its tip, so we must be patient and observe the progress it is making through its journey.